2020
DOI: 10.3390/mi11090790
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulations of Microreactors for the Hydrolysis of Cellobiose to Glucose by β-Glucosidase Enzyme

Abstract: The enzymatic hydrolysis of lignocellulosic biomass-derived compounds represents a valid strategy to reduce the dependence on fossil fuels, with geopolitical and environmental benefits. In particular, β-glucosidase (BG) enzyme is the bottleneck in the degradation of cellulose because it catalyzes the hydrolysis of cellobiose, a known inhibitor of the other cellulolytic enzymes. However, free enzymes are unstable, expensive and difficult to recover. For this reason, the immobilization of BG on a suitable suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…With this enzymatic multi-channel microreactor, we achieved a p-NP production of 0.074 µmol/min, which is 4.6-fold higher than that observed in the single-channel microreactor (0.016 µmol/min for the single-channel microreactor). It is worth noting that further optimization of the enzymatic microreactor performance could be achieved through CFD simulations as indicated in the work of Venezia et al regarding β-glucosidase [59].…”
Section: Development Of a Multi-channel Microreactormentioning
confidence: 99%
“…With this enzymatic multi-channel microreactor, we achieved a p-NP production of 0.074 µmol/min, which is 4.6-fold higher than that observed in the single-channel microreactor (0.016 µmol/min for the single-channel microreactor). It is worth noting that further optimization of the enzymatic microreactor performance could be achieved through CFD simulations as indicated in the work of Venezia et al regarding β-glucosidase [59].…”
Section: Development Of a Multi-channel Microreactormentioning
confidence: 99%
“…The release of glucose by β-glucosidases is vital because glucose is a treasure trove of energy and a crucial building block for the synthesis of biofuels. It has been demonstrated that immobilizing β-glucosidases on appropriate substrates enhances their catalytic activity, which may have consequences for a range of industrial uses, such as the generation of biofuel [41], [42], [43].…”
Section: Endoglucanases and Exoglucanasesmentioning
confidence: 99%
“…Optimal operating conditions and appropriate reactor design, integrating kinetic parameters, can be computationally guided to avoid time‐consuming and expensive experiments. Several examples of model‐based design optimization methods have been published [95–98] …”
Section: Immobilized Enzyme Reactors: a Portfolio Of Optionsmentioning
confidence: 99%